Kebijakan Kombinatif Kepemimpinan Digital Kepala Sekolah Dasar Berbasis Teknologi pada Masa Pandemi Covid-19 - Moh. Muslim; Mohammad Zaini (State Islamic Institute of Madura, 2021)
Primary school principal combinative policies become a crucial problem during the Covid-19 pandemic. Covid-19 is an urgent problem, has a global scale and with a wide impact, include schools which is affected by the presence of covid-19. The government policy to prevent the spread of the covid-19 outbreak is closing these schools and implement a distance learning process. The research objective is to investigate the combinative policies of primary school principals to face Covid-19 deeply. The research method used a qualitative approach with the type of case study research. Data collection technique were observation and interviews. Data analysis used the interactive technique of Miles and Huberman. The conclusion of this study is the leadership digital policy of primary school principals to face Covid-19 pandemic situation are: (1) administrative services, (2) learning process and (3) communication with parents of students.